Clinical Impact of Rapid Recurrence in Oral Tongue Squamous Cell Carcinoma and a Nomogram for Early Identification of High-Risk Patients - Younghac Kim; Eun-Hye Kim; Man Ki Chung; Han-Sin Jeong; Young-Ik Son; Jinyong Kim; Nayeon Choi (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. This study investigated the effects of clinicopathological variables on rapid recurrence (defined as recurrence within 3 months) in oral tongue squamous cell carcinoma (OTSCC) and developed prediction models using multiple data combinations.Methods. A total of 944 patients with OTSCC were divided into two groups according to recurrence timing: the rapid recurrence group (RRG, n=89) and the non-rapid or no-recurrence group (n=855). Treatment-related variables were collected and analyzed to identify factors associated with overall survival (OS) and rapid recurrence. A logistic regression–based prediction model was developed to estimate the probability of rapid recurrence. Model performance was evaluated using 10-fold cross-validation, leave-group-out cross-validation, and calibration analysis.Results. Lower OS rates were observed with increasing age, advanced T (T3–4) and N (N1–3) stages, higher maximum preoperative positron emission tomography standardized uptake value (PET SUVmax), and rapid recurrence. In multivariable logistic regression analysis, advanced T (T2–T4) and N3 stages, positive resection margins, and higher PET SUVmax were associated with rapid recurrence, whereas postoperative chemoradiation demonstrated a protective effect. A nomogram was constructed to facilitate individualized risk estimation by integrating these clinical variables.Conclusion. Rapid recurrence was strongly associated with poor oncological outcomes in OTSCC. The validated prediction model, incorporating imaging and pathological variables, may help identify high-risk patients and support tailored treatment and surveillance strategies.